Estudo toxicológico pré-clínico do extrato hidroalcoólico Das partes aéreas de zornia brasiliensis vog. (fabaceae) - Batista, Tatiane Mota (2015)
Medicinal plants are used in the treatment of various diseases, often indiscriminately, without prior knowledge of possible toxic effects due to their use. In this context, it is essential to carry out toxicological studies of medicinal plants. Zornia brasiliensis (Fabaceae), popularly known as "urinária", "urinana" and "carrapicho", is used by the population as a diuretic. Previous studies reported antioxidant activity and cytotoxicity in brine shrimp larvae. As there are no reports in the literature of its possible in vivo toxicity, the assessment of the toxicological profile is essential for safe use by the population as well as to support the conduct of clinical trials and subsequently the production of an herbal formulation. Thus, this study aimed to evaluate the preclinical toxicity of alcoholic extract of aerial parts of Zornia brasiliensis (EHZB). The value of HC50 obtained in hemolysis assay was 1.954 (1840-2074) / mL, demonstrating that the extract has low toxicity in mouse erythrocytes. During the preclinical acute toxicity test, there were no deaths nor behavioral changes in mice treated with 2000 mg / kg EHZB. There was a significant decrease in feed intake in male animals compared to the control group, however, there was no significant change in weight gain of animals, which showed weight regain after the treatment. No significant difference was observed in the organs indexes (heart, liver, kidneys, spleen and thymus) after acute treatment with EHZB. As regards the evaluation of preclinical repeated dose toxicity (28 days), death was no evidenced in animals treated with the EHZB (250, 500 and 1000 mg / kg) as well, there were no significant changes in weight gain and body temperature of the animals. The EHZB administration resulted in a significant increase in AST and ALT activities in male animals (1000 mg / kg) and in female animals treated with all doses there was increased ALT activity, suggesting the induction of hepatic toxicity by the extract. However, no significant clinical finding was observed in liver histopathology, suggesting that these changes were minor and not damaged the tissue structure. Changes in hematological parameters and exploratory activity were demonstrated, especially with the higher dose of the extract. The results did not show any change in the index of the organs, nor significant changes were revealed in the histopathological study in liver and kidneys. Moreover, EHZB showed no genotoxic activity in vivo, evaluated by micronucleus test in peripheral blood (2000 mg / kg). The data shows that EHZB has low pre-clinical toxicity.